Phase and frequency locking of 0.1-Hz oscillations in heart rate and baroreflex control of blood pressure by breathing of linearly varying frequency as determined in healthy subjects - Karavaev, A. S.; Kiselev, A. R.; Gridnev, V. I.; Borovkova, E. I.; Prokhorov, M. D.; Posnenkova, O. M.; Ponomarenko, V. I.; Bezruchko, B. P.; Shvartz, V. A. (Human physiology, 2013)
Functional interaction was studied between the subsystems that ensure autonomic control of the heart rate (HR) and blood pressure (BP) and give rise to 0.1-Hz oscillations in R-R intervals (RRI) and photoplethysmogram (PPG). Twenty-five recordings were obtained from 18- to 32-year-old healthy persons (six women and nineteen men). The RRI and PPG were recorded simultaneously while the respiration rate of a subject in the sitting position increased linearly from 0.05 Hz to 0.25 Hz within 25 min. Phase and frequency locking of 0.1-Hz oscillations by breathing proved to be possible in both RRI and PPG. The intervals of phase and frequency locking of oscillations by respiration differed in duration and relative position. These distinctions suggest that the mechanisms of autonomic 0.1-Hz control of HR and BP are functionally independent.